Early electroretinografic changes in elderly RA patients treated with hydroxychloroquine - L. Cavagna; P. Rossi; L. Bogliolo; E. Antoniazzi; C. Gelmi; R. Caporali; C. Montecucco (PAGEPress Publications, 2002)
Objective: to evaluate the effectiveness of fundoscopy, electrooculography, electroretinogram and visually evoked potentials in early detection of hydroxychloroquine retinal toxicity in RA patients and to evaluate the influence of patients' age, drug dosage, concomitant therapy (prednisone and methotrexate) and serum creatinine levels in the development of this side effect. Methods: from september to december 1999, we have enrolled 32 RA patients (13 males, 19 females) starting hydroxichlorochine treatment. The patients underwent regular ophthalmological examination (fundoscopy, electro-oculography, electro-retinogram and visually evoked potentials) every 4 months. Disease activity was evaluated every two months by clinical and routine serological examination. Results: no patients developed retinopathy during 1 year's follow-up; fundoscopy, electrooculography, and visually evoked potentials did not vary from the baseline. On the other hand, electroretinogram showed early alterations of scotopic and photopic response; moreover a significant statistical correlation between patients' age (more than 65 years) and b1 photopic wave increase (p < 0,05) was observed. No correlation was found between the developement of electro- retinographic alterations and hydroxychloroquine dosage, concomitant therapy and serum creatinine levels Conclusion: our data show the inefficacy of fundoscopy, electrooculography and visually evoked potentials in early detection of hydroxychloroquine retinopathy. On the other hand electroretinogram allows early detection of retinal alterations during hydroxychloroquine treatment, in patients older than 65 years.